Peran Homeschooling Dalam Membangun Keterampilan Sosial Anak Di Era Digital - Nahdia Til Fauziah; Putri Rahmi; Gusmaneli (CV. ITTC INDONESIA, 2024)
The integration of technology in homeschool learning has great potential to support the development of children's social skills. In the digital era, technology provides broad access to learning resources and social interaction through online platforms. Despite this, challenges such as social isolation and lack of in-person interaction remain. The flexibility of homeschooling allows parents to customize the curriculum and integrate social activities, so children can learn from hands-on experiences. The role of parents and the community is very important in creating an environment that supports social interaction. With the right approach, including timing of technology use and education in digital ethics, homeschooled children can develop the social skills necessary to interact well in society. In conclusion, homeschooling can be an effective alternative in building children's social skills in the digital era, as long as it is supported by good guidance from parents and the community.